2022
DOI: 10.1044/2022_jslhr-22-00024
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Mandarin Lexical Tone Perception in Quiet and Noisy Contexts: The Influence of Visual Cues and Speech Rate

Abstract: Purpose: Armed with the theory of embodied cognition proposing tight interactions between perception, motor, and cognition, this study aimed to test the hypothesis that speech rate–altered Mandarin lexical tone perception in quiet and noisy environments could be affected by the bodily dynamic cross-modal information. Method: Fifty-three adult listeners completed a Mandarin tone perception task with 720 tone stimuli in auditory-only (AO), auditory–facial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…Particularly, for Tone 3, the larger and faster head-raising movement after head dipping in clear than plain speech is aligned with the dynamic nature of Tone 3 (with a falling-rising pitch contour), thus enhancing the Tone 3-specific characteristics. This is consistent with the previous findings of a greater accuracy in visual perception of Tone 3 compared to that of the other tones in Mandarin ( Hannah et al, 2017 ; Li et al, 2022 ). In contrast, in Tone 4 clear speech, a larger and faster head raise occurred after head falling (that is, after the completion of Tone 4), which consequently approximated a Tone 3 movement trajectory and caused confusion.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Particularly, for Tone 3, the larger and faster head-raising movement after head dipping in clear than plain speech is aligned with the dynamic nature of Tone 3 (with a falling-rising pitch contour), thus enhancing the Tone 3-specific characteristics. This is consistent with the previous findings of a greater accuracy in visual perception of Tone 3 compared to that of the other tones in Mandarin ( Hannah et al, 2017 ; Li et al, 2022 ). In contrast, in Tone 4 clear speech, a larger and faster head raise occurred after head falling (that is, after the completion of Tone 4), which consequently approximated a Tone 3 movement trajectory and caused confusion.…”
Section: Discussionsupporting
confidence: 93%
“…Further research has shown that, similar to the observation for segmental distinctions (Sumby and Pollack, 1954), visual tonal information may become more prominent in situations where auditory information is degraded and more difficult to access, such as in the presence of background noise or with a hearing impairment. For example, for Mandarin and Thai tones, while there was no difference in native perceivers' identification in the AV and the AO modes, an advantage for the AV mode over the AO mode became apparent when the same stimuli were presented in babble or cafeteria noise (Mixdorff et al, 2005;Burnham et al, 2015;Hannah et al, 2017;Li et al, 2022). Similarly, when the acoustic signal of Mandarin tones was degraded to resemble cochlear-implant (CI) speech, Mandarin perceivers did significantly better in the CI-simulated AV condition than in the CI-simulated AO condition (Smith and Burnham, 2012).…”
Section: Tone Perception and Visual Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies are urgently called to clarify the relationship between the McGurk illusion and the other measurements of audiovisual integration. Besides, as working memory seemed not to be an important factor in predicting audiovisual speech perception among adults (Li et al, 2022), this factor was not addressed by the current study. Considering this might not be the case in children, future studies with working memory taken into account are also warranted.…”
Section: Limitations and Future Directionsmentioning
confidence: 66%